2023
DOI: 10.1002/hbm.26280
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking recovery in adolescent concussions: Network‐level functional connectivity alterations associated with motor deficits

Abstract: Adolescents who are clinically recovered from concussion continue to show subtle motor impairment on neurophysiological and behavioral measures. However, there is limited information on brain–behavior relationships of persistent motor impairment following clinical recovery from concussion. We examined the relationship between subtle motor performance and functional connectivity of the brain in adolescents with a history of concussion, status post‐symptom resolution, and subjective return to baseline. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…Rapid reconfigurations of network connectivity patterns generate neural signals that are highly variable, which produce consistency in behavioral responses ( 37 , 38 ). Conversely, reduced default mode network deactivation is believed to result in attention lapses that produce inconsistency in motor output ( 14 ). Our finding of an association between elevated Step RT-IIV with CLEI (males ≥0.282 and females ≥0.301) is consistent with evidence for the interpretation of high RT-IIV as a behavioral correlate of neural impairment ( 20 , 27 29 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rapid reconfigurations of network connectivity patterns generate neural signals that are highly variable, which produce consistency in behavioral responses ( 37 , 38 ). Conversely, reduced default mode network deactivation is believed to result in attention lapses that produce inconsistency in motor output ( 14 ). Our finding of an association between elevated Step RT-IIV with CLEI (males ≥0.282 and females ≥0.301) is consistent with evidence for the interpretation of high RT-IIV as a behavioral correlate of neural impairment ( 20 , 27 29 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that VR testing can detect a potentially modifiable contributor to elevated injury susceptibility through documentation of a prospective association between pre-participation perceptual–motor performance and subsequent injury occurrences. A substantial body of evidence has established that concussion effects can persist for months or years beyond clinical recovery and return to sport participation ( 7 , 14 , 17 , 21 ). Numerous researchers have presented evidence supporting a need for more stringent criteria to determine post-concussion readiness for return to sport ( 2 , 3 , 5 , 24 , 30 ) and a need for periodic risk screening of all athletes with a test that imposes sufficient cognitive and motor challenge to reveal subtle deficits ( 12 , 14 , 23 , 31 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-immersive VR methods project a simulated environment onto a screen or computer monitor that is viewed within the surrounding real environment, whereas immersive VR methods project the user into a simulated three-dimensional environment through a head-mounted display that completely removes visual awareness of the real environment (Müller et al, 2023; Santos et al, 2020). A growing awareness of the limitations of existing clinical tests for detecting subtle performance deficiencies among athletes has created a critical need for new clinical measures that will identify those with elevated injury risk (Crasta et al, 2023; Wong et al, 2023). Compared to standard clinical tests of neurocognitive and neuromuscular function, VR can provide greater control of visual stimuli (e.g., location, duration, speed of movement and closer coupling between perceptual and motor responses) (Harris et al, 2020; Müller et al, 2023).…”
Section: Introductionmentioning
confidence: 99%